The Use of the Gamelan-Room Website in Ethnomatics-Based Geometry Instruction for Second-Grade Elementary School Students - Zumrotus Sa'diyah; Zaenal Abidin; Wiryanto Wiryanto (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2025)
This study aims to determine the effectiveness of using the Gamelan-Room website as a learning medium on student achievement in the topic of plane figures. This study employed a quasi-experimental method using a nonequivalent control group design. The study involved two groups: a control class and an experimental class. Both groups were administered pretests and posttests to observe differences in learning outcomes before and after the intervention. The research subjects were second-grade students, with 26 students in the control class and 26 students in the experimental class. The results of the normality and homogeneity tests indicated that the data met the requirements for hypothesis testing. The results of the independent samples t-test showed that the control group’s average pretest score of 67.0 increased to 78.5 on the posttest, while the experimental group’s average pretest score of 60.5 increased to 84.0 on the posttest. The increase in learning outcomes for the experimental class was greater than that of the control class. From these research results, it can be concluded that the use of the Gamelan-Room website as a visual learning medium for the shapes and characteristics of plane figures proved to be effective in improving students’ mathematics learning outcomes compared to conventional instruction.